2016
DOI: 10.1371/journal.pone.0160301
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Finger Joint Biomechanics by Applying Equal Force to Flexor Tendons In Vitro Using a Novel Simultaneous Approach

Abstract: BackgroundThe flexor digitorum superficialis (FDS) and flexor digitorum profundus (FDP) are critical for finger flexion. Although research has recently focused on these tendons’ coactivity, their contributions in different tasks remain unclear. This study created a novel simultaneous approach to investigate the coactivity between the tendons and to clarify their contributions in different tasks.MethodsTen human cadaveric hands were mounted on our custom frame with the FDS and FDP of the third finger looped thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The maximum flexion force at the DP segment was approximately 7.4 N (Fig. 7 (A)), which is larger than the minimum force for full flexion of finger joints (7 N, [30]). Therefore, only Model 2 has the potential of assisting a full thumb flexion.…”
Section: ) Comparison Among 3c-actsmentioning
confidence: 78%
“…The maximum flexion force at the DP segment was approximately 7.4 N (Fig. 7 (A)), which is larger than the minimum force for full flexion of finger joints (7 N, [30]). Therefore, only Model 2 has the potential of assisting a full thumb flexion.…”
Section: ) Comparison Among 3c-actsmentioning
confidence: 78%
“…These studies all reported on loading forces during flexion. Loading forces on each joint in full flexion in the study by Yang et al ranged from 1.69 to 7.93 N [25]. The forces in the study by Kursa et al [27] ranged from 1.3 to 4 N in FDP tendons and 1.3-8.5 N in FDS tendons, and Edsfeldt et al [28] reported forces of up to 13 N. Although the lock constraints may have meant that the model in our study has under-predicted the highest values for force, the results for the healthy FDP observed a trend which appears consistent with the maximum force values reported in the literature.…”
Section: Discussionmentioning
confidence: 92%
“…There is agreement in the literature that tension in the FDP tendon is greater than that in the FDS tendon for healthy fingers [25,27]. More specifically, in a study by Lu et al, tension generated during passive extension modelling was estimated in the FDP tendon as 1.41 to 22.93 N compared to 0.78 to 11.97 N in the FDS tendon [23].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The content of collagen in the tendon, especially type I collagen, is related to the biomechanical property of repaired tendon. The tendon must be completely healed through collagen fiber deposition, molding, and maturation[ 31 , 32 ]. This study proved that the order of fibroblasts and collagen fibers in the amniotic tendon group was significantly better than that in the control group at the 2nd week after operation.…”
Section: Discussionmentioning
confidence: 99%